Los modelos pedagógicos y su influencia dentro de las etapas de enseñanza-aprendizaje en el área de ciencias naturales, aplicados a los y las estudiantes de séptimo grado del subnivel de básica media, de educación general básica, del Plantel Central Ciudad de Huaquillas, período 2014-2015 - Ajila Rueda, Bayron Augusto (2015)
The present research is titled “The pedagogic standards and its influence within the teaching-learning stages in the natural sciences subject applied to male and female students who are in the seven year of the subdivision in the basic level, inserted in the basic-general education from the central campus “City of Huaquillas”, school year 2014-2015”, the general aim of this research is to get to know the influence of the pedagogic standards within the teaching-learning stages in the natural sciences subject applied to male and female students who are in the seven year of the subdivision in the basic level, inserted in the basic-general education from the central campus “City of Huaquillas”, school year 2014-2015. The methods used in this process were: descriptive, deductible, inductive, statistical and biographical. Likewise, it was worked with practical collection techniques also called “of field” as a survey supported by a close-ended questionnaire and an interview with some already-formulated questions. It was worked with a 53-student population and two educators. Through the tabulation was possible to obtain the aimed outcomes and based on them it was helpful to get a conclusion that the educators base their knowledge on the traditional standards when sharing to their students, blocking the learners to gain updated knowledge and also do not use the “tic” as support. For this reason, it is formulated alternative settings in order to motivate educators in using new pedagogic standards to secure the teaching-learning process in the natural science area, innovating the use of the active techniques and strategies either in or out of the classrooms. It can be achieved through updating the educators to help to make the learning process an enjoyable practice so as to motivate students to open their creativity and originality and in this way give solution to the issue established at the beginning of the research